The Impact of Perceived Organizational Support (POS) for Increasing the Intention to Stay: A Systematic Review - Mira Melynda Prakosa; Nisa Dewanti; Sena Wahyu Purwanza (Jurnal Ners, 2019)
Background: Nurse turnover is a problem that occurs in hospitals. The high turnover of nurses in health facilities can have a negative impact on the needs of the patients and on the quality of the health services. The turnover of nurses thus becomes a serious challenge to the efficiency, effectiveness and productivity of the health services. The aim of the systematic review was conducted to examine the impact of perceived organization support when it came to increasing the intention to stay.Method: A systematic search was conducted using articles from Scopus, Science Direct and SAGE. The search identified 15 original articles and full texts published between 2014 and 2019.Result: Nurses with high perceived organizational support with their organization have a lower intention to leave the organization. POS is the key predictor of turnover intention.Conclusion: POS can reduce turnover, especially for nurses. The positive perception of the organization can decrease turnover intention. POS that is felt strongly will affect the work performance of the nurses by increasing their intention to stay. This can the reduce hospital costs when it comes to having to recruitment new nurses.